Effects of Fluoride on Submandibular Glands of Mice: Changes in Oxidative Biochemistry, Proteomic Profile, and Genotoxicity - Lima, Leidiane Alencar de Oliveira; Miranda, Giza Hellen Nonato; Aragão, Walessa Alana Bragança; Bittencourt, Leonardo Oliveira; dos Santos, Sávio Monteiro; de Souza, Michel Platini Caldas; Nogueira, Lygia S.; de Oliveira, Edivaldo Herculano Corrêa; Monteiro, Marta Chagas; Dionizio, Aline; Leite, Aline Lima; Pessan, Juliano Pelim; et al. (Frontiers in Pharmacology, 2021)
Despite fluoride (F) is currently the basis for preventing dental caries, changes in cell processes in different types of tissues have been associated with excessive exposure to this ion. Thus, this study evaluated the effects of exposure to f on the submandibular glands of mice, through the analysis of biochemical, proteomic, and genotoxic parameters. Mice (n = 30, 21 days old), were divided into three groups: administration of drinking water at 10 and 50 mg F/ L, during 60 days, while the control group was given deionized water. The submandibular glands were collected after the treatment period. The results showed that F, at both concentrations, was able to increase the concentration of thiobarbituric acid reactive substances in a possible dose-response effect, while there was a reduction in glutathione, in addition to promoting changes in the proteomic profile mainly regarding the cytoskeleton and cellular activity in the glandular tissue. As for the DNA integrity, significant changes were promoted only by the highest concentration (50 mg F/L). These findings reinforce the importance of permanent monitoring of F concentrations in the drinking water, and of strategies to minimize F intake from other sources, to achieve maximum preventive/therapeutic effects and avoid potential side effects.